2013
DOI: 10.1109/tmm.2013.2241043
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing Multimedia QoE Evaluation: A Trusted Framework

Abstract: Crowdsourcing has emerged in recent years as a potential strategy to enlist the general public to solve a wide variety of tasks. With the advent of ubiquitous Internet access, it is now feasible to ask an Internet crowd to conduct QoE (Quality of Experience) experiments on their personal computers in their own residences rather than in a laboratory. The considerable size of the Internet crowd allows researchers to crowdsource their experiments to a more diverse set of participant pool at a relatively low econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 65 publications
0
44
0
Order By: Relevance
“…Studies from literature have shown that using crowdtesting for the QoE assessment of a wide range of video applications can deliver results similar to traditional testing in the lab environment: Keimel et al have shown in [21], [23] that crowdtesting delivers results within the acceptable inter-lab variation between different testing labs for standard conforming QoE assessment, Chen et al discussed crowdtesting for audio-visual QoE of Internet-based applications in [24], [25], which was discussed more in detail by Wu et al in [26], and Hossfeld et al applied crowdtesting to the influence of stalling events [20] and initial delays [27] on the QoE in video streaming applications. For pairwise comparison QoE tests, Xu et al.…”
Section: Qoe Crowdtesting With Emphasis On Video Applicationsmentioning
confidence: 99%
“…Studies from literature have shown that using crowdtesting for the QoE assessment of a wide range of video applications can deliver results similar to traditional testing in the lab environment: Keimel et al have shown in [21], [23] that crowdtesting delivers results within the acceptable inter-lab variation between different testing labs for standard conforming QoE assessment, Chen et al discussed crowdtesting for audio-visual QoE of Internet-based applications in [24], [25], which was discussed more in detail by Wu et al in [26], and Hossfeld et al applied crowdtesting to the influence of stalling events [20] and initial delays [27] on the QoE in video streaming applications. For pairwise comparison QoE tests, Xu et al.…”
Section: Qoe Crowdtesting With Emphasis On Video Applicationsmentioning
confidence: 99%
“…Two frameworks often utilised are the Quadrant of Euphoria by Chen et al [14,20,21] and the QualityCrowd framework by Keimel et al [16] that is also used in this contribution. For a detailed discussion about web-based crowdsourcing frameworks for subjective quality assessment we refer to the survey in [22].…”
Section: Subjective Evaluation Via Crowdsourcingmentioning
confidence: 99%
“…The Quadrant of Euphoria is a web-based online crowdsourcing platform for the QoE evaluation of audio, visual, and audio-visual stimuli proposed by Chen et al in [12], [13] and extended by Wu et al in [14] .…”
Section: A Quadrant Of Euphoriamentioning
confidence: 99%